Agroforestry typology and its implications on surrounding south region of Gunung Merapi National Park, Java, Indonesia - Supryanto, Priyono; Hamzah, Mohd. Zaki; Mohamed, Azmy; Alias, Mohamad Azani (Forestry Department Peninsular Malaysia, 2010)
The surrounding characteristics land use for the new national park of Mount Merapi in the southern region are dominated by agroforestry practice. Based on the situation, a review of its agroforestry status is very important in an early step in a perspective collaboration approach between the local community and the national park. The objectives of this study were to determine the typology of agroforestry and its implications on Gunung Merapi National Park (GMNP). The study used a survey approach with a population unit community which practises agroforestry in Kaliadem and Jambu Village. Purposive random sampling was employed where the respondents were randomly chosen based on the social status data retrieved from the local authorities. Meanwhile, measurement of stand structure was done by census technique on all land types by the selected respondents. Social economic aspect was assessed using a thorough interview with each chosen respondent. In particular, clustering agroforestry practice, with a K-mean cluster and a similar pattern of interaction among land types with GMNP, was identified using an ordination with Multidimensional Scaling (MDS). The results showed that agroforestry has been practised in home garden, dry field and village lands, as proven by the domination of agroforestry based on grass (AFG). Based on the AFG in private lands and the level of emphasis given on the GMNP, the typology of agroforestry and its implications on the GMNP could be grouped into three different clusters labelled as intensive agroforestry, semi-intensive agroforestry and conventional agroforestry. Therefore, an initiation buffer zone management on the areas surrounding the GMNP could be done through private land optimisation with a focus on intensive agroforestry.